A non-precious metal carbon-based nanocatalyst and its preparation method and application
By using the combination of copper-nickel core-shell nanostructure and carbon black in fuel cell catalysts, the problems of high cost and poor stability of precious metal catalysts are solved, and low-cost, efficient and stable catalytic performance is achieved, which is suitable for catalysis of various biomass small molecules.
Patent Information
- Application Number
- CN202211068894.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-30
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2042-08-30
AI Technical Summary
Existing fuel cell catalysts mostly use precious metals, resulting in high costs, high energy consumption and poor stability, limiting the commercial application of biomass fuel cells.
By mixing the copper source and nickel source with a reducing agent, the copper-nickel core-shell nanostructure was synthesized under the protection of surfactant, and evenly dispersed after adding carbon black, oxidation and reduction treatment were performed to prepare a copper-nickel nanocatalyst with partial oxidation supported by carbon.
It achieves low-cost, efficient and stable catalytic performance, and is suitable for catalysis of various biomass small molecules, especially in the process of glycerol catalysis, which shows extremely high stability and recovery ability.
Smart Images

Figure CN115425238B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalyst preparation, and in particular relates to a non-precious metal carbon-based nanocatalyst and a preparation method and application thereof. Background Art
[0002] At present, with the excessive use of fossil fuels and the growing energy demand of mankind, mankind is facing increasingly severe social problems such as energy crisis and environmental pollution. Therefore, researchers are working hard to develop and use new sustainable energy to replace fossil fuels. Every year, biomass diesel derived from vegetable oils and animal fats is as high as about 30 million cubic meters, while producing 10% of by-product glycerol, and the output is increasing at a rate of ~9.3% / year. This type of biomass small molecule has the advantages of a wide source of raw materials, good environmental performance, and renewability, and is a top-level cornerstone green energy chemical.
[0003] Fuel cells, which can effectively convert the above-mentioned biomass alcohol into electrical energy, are a new renewable energy technology that has attracted widespread attention due to its high energy density, low pollution and simple operation. So far, one of the key factors hindering the large-scale commercialization of biomass fuel cells and even other fuel cells is the electrode catalyst. On the one hand, current high-performance fuel cell catalysts are mostly based on precious metal materials such as platinum. Platinum metal has low reserves on the earth and scarce resources, and the cost of catalysts accounts for nearly half of the total cost of the battery. In addition, precious metal catalysts such as platinum are easily adsorbed by intermediates such as CO formed during the oxidation of methanol, resulting in catalyst poisoning and deactivation. Based on the above two survey results, looking for new, efficient and stable non-precious metal catalysts can achieve the goal of low cost and improve the overall performance of the battery in the hope of meeting the requirements of future commercialization. Transition metals have attracted much attention as an alternative metal that can maintain high catalytic activity and have good anti-toxicity.
[0004] Patent CN101516550B discloses a core-shell catalyst particle and its preparation method. The catalyst particle median particle size (d core + shell) used is 20-100 nm, and the shell layer is a core-shell catalyst represented by Pt (the number of atomic layers of the shell layer is at least 3 or more), which relatively reduces the precious metal Pt loading by 45-75%, but does not mention its specific electrochemical activity index. In addition, due to the large size of the inner core particle size, the precious metal is also a relatively large particle size, and the cost investment is relatively high. The document [Nature Materials, 2008.7 (4): p.333-338.] reports a core-shell catalyst (Ru@Pt) in which 1-2 atomic layers of Pt are loaded on the surface of Ru particles with a diameter of 2-4 nm. When the catalyst uses the same 1.0wt% Pt loading as other single metal and alloy catalysts, it is the only one that exhibits particularly outstanding low-temperature (about 20-30°C) CO oxidation performance. However, a large amount of organic solvent toluene is used in the synthesis process of the core Ru, and the core Ru itself is also a precious metal. Patent CN102500365A reports a method for preparing a core-shell structure catalyst for low-temperature fuel cells. First, hydrothermal reduction of polyol-water phase is carried out in a high-pressure reactor at 100-160°C for 4-12 hours, and then heat treatment is carried out in an inert atmosphere at 100-150°C to obtain a carbon-supported metal core catalyst as a precursor for loading precious metals. Then, a precious metal shell is loaded on the core by an impregnation reduction method, a high-pressure organic sol method, a microwave method or an electrodeposition method to obtain a core-shell catalyst. When preparing the metal core, the hydrothermal process is cumbersome and time-consuming, and the stabilization effect on the non-precious metal core is average. Summary of the invention
[0005] The present invention aims to develop a new non-precious metal carbon-based nanocatalyst with extremely strong stability in catalyzing small molecules of biomass. The copper source, the nickel source and the reducing agent are mixed, and a copper-nickel core@shell nanostructure (Cu@Ni) is synthesized under the protection of a surfactant. After adding carbon black, the mixture is evenly dispersed to form a carbon black-loaded copper-nickel core@shell nanostructure (Cu@Ni-C), which is then oxidized in air to form Cu@NiO. y -C. After hydrogen reduction, the carbon-supported partially oxidized copper-nickel nanocatalyst (pr-Cu@NiO y -C) to solve the problems of traditional catalysts that mostly use precious metals, have high manufacturing costs, high energy consumption, and poor stability.
[0006] In order to achieve the above object, the technical solution of the present invention is achieved as follows:
[0007] A method for preparing a non-noble metal carbon-based nanocatalyst comprises the following steps:
[0008] (1) mixing and dispersing a copper source, a nickel source, a reducing agent and a surfactant, heating and reacting the mixture under the protection of an inert atmosphere, washing the mixture with an organic solvent after the reaction, and drying the mixture to obtain a copper-nickel composite material;
[0009] (2) mixing and dispersing the copper-nickel composite material obtained in step (1) with the carbon material, and introducing oxygen under a first temperature condition to carry out an oxidation reaction to obtain an oxidation product;
[0010] (3) introducing hydrogen into the oxidation product obtained in step (2) under a second temperature condition to carry out a reduction reaction to obtain the non-precious metal carbon-based nanocatalyst.
[0011] In step (1), the copper source is copper acetylacetonate, the nickel source is nickel chloride, the reducing agent is ascorbic acid, and the surfactant is oleylamine.
[0012] Preferably, the mass ratio of the copper in the copper source to the nickel in the nickel source is 1 to 5.5:1.
[0013] Specifically, in step (1), the conditions for heating the reaction under the protection of an inert atmosphere are: first react at a reaction temperature of 170° C. for 2 h, then increase the reaction temperature to 200° C., and react at 200° C. for 1 h.
[0014] Preferably, in step (1), the organic solvent is a mixture of cyclohexane and anhydrous ethanol, and the volume ratio of the mixture is 7: 1. The organic solvent is used to wash away the surfactant and impurities such as the remaining metal salt.
[0015] Preferably, in step (2), the carbon material is carbon black, and the mass ratio of the carbon black to the copper-nickel composite material is 1.5:1.
[0016] Specifically, in step (2), the first temperature condition is: raising the reaction temperature to 400°C, keeping at 400°C for 1 hour, and the heating rate is 6°C / min.
[0017] Specifically, in step (3), the second temperature condition is: raising the reaction temperature to 200°C, keeping it at 200°C for 1 hour, and the heating rate is 3°C / min.
[0018] The present invention also provides a non-noble metal carbon-based nanocatalyst prepared by the preparation method.
[0019] The copper-nickel carbon-based nanocatalyst (pr-Cu@NiO y -C) consists of partially oxidized copper-nickel nanoparticles with a particle size ranging from 5 to 20 nm, and the surface of the nanoparticles contains nickel oxide.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The preparation method of the present invention is simple and convenient. It only needs to synthesize the copper-nickel core-shell nanostructure (Cu@Ni) by a solvothermal method, load carbon black and perform redox reaction treatment. The synthesis process is safe and green, and no solvent needs to be added, thus avoiding the problems of high cost, high energy consumption, poor stability and great safety hazards existing in traditional synthesis methods.
[0022] (2) The present invention uses transition metal materials, has low production cost, high safety, low energy consumption, and the temperature of the entire preparation process is no higher than 400°C.
[0023] (3) The non-precious metal carbon-based nanocatalyst prepared by the present invention has a regular morphology and a relatively obvious core-shell structure.
[0024] (4) pr-Cu@NiO prepared by the present invention y -C exhibits excellent catalytic performance and has promising application prospects when assembled into fuel cell devices. In addition, this catalyst has obvious catalytic oxidation activity for a variety of different biomass small molecules and can be applied to a variety of biomass fuel cell fields.
[0025] (5) The most notable feature of the non-precious metal carbon-based nanocatalyst prepared by the present invention is that it has extremely high stability in the process of catalyzing small molecules of biomass. In the process of catalyzing glycerol, the catalytic performance slowly decreases over time, and when the concentration of the glycerol solution is changed, it can be clearly observed that the catalytic performance of the catalyst is restored to the initial state, proving that the main reason for the decrease in catalytic performance in the glycerol catalytic process is the decrease in glycerol concentration. In the 15,000-cycle CV cycle test, the solution was changed three times in the middle, and the catalytic performance was able to return to the initial value, which fully proves the super stability of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the synthesis of the non-precious metal carbon-based catalyst described in an embodiment of the present invention.
[0027] Figure 2 This is the SEM characterization spectrum of the non-precious metal carbon-based catalyst described in Example 1 of the present invention.
[0028] Figure 3 This is the LSV test graph of Example 1 of the present invention in various biomass small molecules.
[0029] Figure 4 These are LSV diagrams of the copper-nickel nanocatalysts of Examples 1-3 of the present invention in different biomass small molecule solutions.
[0030] Figure 5 Example 1-3pr-Cu@NiO of the present invention y -C and XRD patterns of materials during its synthesis.
[0031] Figure 6 The cyclic voltammetry test diagram of the products prepared in Examples 1-3 of the present invention in a glycerol solution after being assembled into electrodes.
[0032] Figure 7 IT test diagram of the products prepared in Examples 1-3 of the present invention in a glycerol solution after being assembled into electrodes and before cyclic voltammetry test.
[0033] Figure 8 IT test diagram of the products prepared in Examples 1-3 of the present invention in glycerol solution after being assembled into electrodes and subjected to cyclic voltammetry test. DETAILED DESCRIPTION
[0034] Example 1
[0035] pr-Cu@NiO y The synthesis mechanism of -C is as follows Figure 1 As shown, the preparation method is as follows:
[0036] (1) Weigh 66.5 mg of copper acetylacetonate, 264.0 mg of ascorbic acid, 29.75 mg of nickel chloride hexahydrate, and 25 ml of oleylamine;
[0037] (2) Transfer the above products into a round-bottom flask and ultrasonicate for half an hour to make the solution evenly dispersed; install a three-way valve, evacuate and fill the volumetric flask with nitrogen, and ensure that the experiment is carried out in a nitrogen environment;
[0038] (3) The round-bottom flask was placed in an oil bath at 170°C and heated for 2 h. The temperature was then raised to 200°C and reacted for 1 h.
[0039] (4) washing three times with a mixed solution of cyclohexane: anhydrous ethanol = 7:1, placing in a vacuum oven, and drying to obtain a copper@nickel core-shell nanostructured nanocomposite material Cu2@Ni1;
[0040] (5) adding carbon black in a ratio of carbon black to Cu2@Ni1=1.5:1, and placing the mixture in an ultrasonic apparatus for 0.5 to 2 hours to uniformly disperse the mixture to form Cu2@Ni1-C;
[0041] (6) placing the above mixture in a muffle furnace, raising the reaction temperature to 400°C, oxidizing in air at 400°C, keeping the temperature for 1 hour, and heating at a rate of 6°C / min;
[0042] (7) The oxidized product was placed in a tubular furnace, the reaction temperature was raised to 200 °C, and the product was reduced and kept at 200 °C under hydrogen conditions for 1 h at a heating rate of 3 °C / min. The non-precious metal carbon-based nanocatalyst (pr-Cu@NiO y -C).
[0043] Example 2
[0044] This embodiment provides a method for preparing a non-precious metal carbon-based catalyst, which differs from Embodiment 1 in that:
[0045] In step (1), the mass of nickel chloride hexahydrate is weighed to be 59.5 mg.
[0046] The remaining steps and parameters are the same as those in Example 1.
[0047] Example 3
[0048] This embodiment provides a method for preparing a non-precious metal carbon-based catalyst, which differs from Embodiment 1 in that:
[0049] In step (1), the mass of nickel chloride hexahydrate is weighed to be 11.9 mg.
[0050] The remaining steps and parameters are the same as those in Example 1.
[0051] Test Example 1
[0052] (1) The carbon-based copper-nickel alloy nanocatalyst prepared in Example 1 was subjected to morphological analysis to obtain the following Figure 2 The carbon-based copper-nickel alloy nanocatalyst SEM image is shown. Figure 2 Clearly 50 nm-sized Cu@Ni core@shell nanoparticles can be seen.
[0053] (2) Figure 5 The XRD patterns of the copper-nickel alloy nanocatalysts of Examples 1-3 (the ratio of Cu to Ni in Examples 1 to 3 is 2:1, 5.5:1, and 1:1, respectively, wherein the curve Cu2@Ni1 is the XRD pattern of the nanocomposite Cu2@Ni1 prepared in Example 1, the curve Cu2@Ni1 / CB is the XRD pattern of the non-precious metal carbon-based nanocatalyst prepared from the nanocomposite Cu2Ni1 in Example 1, and the curve Cu2@Ni1 / CB is the XRD pattern of the nanocomposite Cu2@Ni prepared in Example 1 11 XRD pattern of the product obtained after oxidation reaction with carbon black). Figure 5 It can be seen that the peak appears between the copper standard card and the nickel standard card, proving the formation of copper-nickel alloy, and the special peak identifies its special crystal form.
[0054] (3) The non-precious metal carbon-based nanocatalyst prepared in Example 1 was assembled into an electrode, and the performance of electro-oxidation and hydrogen evolution of biomass small molecules was tested. The specific assembly method is as follows:
[0055] 2 mg of non-precious metal carbon-based nanocatalyst and 10 μL of Nafion binder were dispersed in 400 μL of isopropanol solution and dispersed evenly by ultrasonication for 0.5 h. The mixture was coated on a glassy carbon electrode and dried naturally for use. The catalyst loading was 0.5 mg / cm 2 , that is, the working electrode is obtained. Mercury-mercuric oxide is used as the reference electrode, platinum mesh is used as the counter electrode, and the electrolyte is 0.1M NaOH solution and 0.1M NaOH+biomass small molecule solution (glycerol, methanol, ethanol, 5-hydroxymethylfurfural).
[0056] Figure 3 It is pr-Cu2@Ni1O y LSV curves of -C in 0.1M NaOH solution and 0.1M NaOH+biomass small molecule solution. Figure 3 It can be seen that pr-Cu2@Ni1O y -C has a catalytic effect on various biomass small molecules, especially in glycerol, where the starting potential is only 0.3V relative to the mercury oxide electrode, and the maximum current in methanol is nearly 3.0mA.
[0057] Figure 4 The LSV diagrams of the three copper-nickel nanocatalysts in different biomass small molecule solutions of Examples 1-3 of the present invention show that the three different proportions of pr-Cu@NiO y -C catalysts showed certain activity in electrooxidation of biomass alcohols, among which pr-Cu2@Ni l O y -C has the highest catalytic activity.
[0058] Figure 6 After the products prepared in Examples 1-3 were assembled into electrodes, cyclic voltammetry tests were performed in 0.1M NaOH+glycerol solution. It was found that the current of the catalyst dropped to about 75% of the initial state after nearly 5000 cycles of catalysis. After pausing to change the solution, it was found that the current value was able to recover to a certain extent, proving that the catalytic performance of the catalyst is extremely stable.
[0059] Figure 7 After the products prepared in Examples 1-3 were assembled into electrodes, they were IT tested in 0.1M NaOH+glycerol solution. We found that after 15,000 seconds of testing, the current of the catalyst decreased, and the remaining current value was more than 75% of the initial current. After pausing to replace the solution, it was found that the current value was able to recover to a certain extent, proving that the catalytic performance of the catalyst is extremely stable.
[0060] In summary, the present invention prepares non-precious metal carbon-based nanocatalysts, and the metals used are all transition metals, which are low in cost, have extremely strong stability and low starting potential, and are suitable for industrial production. Moreover, it can play a catalytic role in a variety of biomass small molecules and can be applied to a variety of energy storage fields.
Claims
1. A method for preparing a non-precious metal carbon-based nanocatalyst, characterized in that: The following steps are involved: (1) mixing and dispersing a copper source, a nickel source, a reducing agent and a surfactant, heating and reacting them under the protection of an inert atmosphere, washing them with an organic solvent after the reaction, and drying them to obtain a copper-nickel composite material; The conditions for the heating reaction under the protection of an inert atmosphere are: first react at a reaction temperature of 170°C for 2 hours, then raise the reaction temperature to 200°C, and react at 200°C for 1 hour; The copper source is copper acetylacetonate, and the nickel source is nickel chloride; The reducing agent is ascorbic acid and the surfactant is oleylamine; The mass ratio of the copper in the copper source to the nickel in the nickel source is 1-5.5:1; (2) mixing and dispersing the copper-nickel composite material obtained in step (1) with the carbon material, introducing oxygen at a first temperature to carry out an oxidation reaction to obtain an oxidation product; The first temperature condition is: raising the reaction temperature to 400°C, keeping at 400°C for 1 h, and the heating rate is 6°C / min; The carbon material is carbon black, and the mass ratio of the carbon black to the copper-nickel composite material is 1.5:1; (3) introducing hydrogen into the oxidation product obtained in step (2) under a second temperature condition to carry out a reduction reaction to obtain the non-precious metal carbon-based nanocatalyst; The second temperature condition is: raising the reaction temperature to 200°C, keeping it at 200°C for 1 hour, and the heating rate is 3°C / min.
2. The preparation method according to claim 1, characterized in that In step (1), the organic solvent is a mixture of cyclohexane and anhydrous ethanol, and the volume ratio of the mixture is 7:
1.
3. A non-noble metal carbon-based nanocatalyst prepared by the preparation method as claimed in claim 1 or 2.
Citation Information
Patent Citations
Core / shell-type catalyst particles and methods for their preparation
CN101516550B
Preparation method of catalyst with core-shell structure for low-temperature fuel cell
CN102500365A
Carbon-loaded Co core-Pt shell nanoparticle catalyst as well as preparation method thereof
CN103537299A
Non-noble metal catalytic material loaded core-shell catalyst, preparation method and application thereof
CN109378482A